Building capacity for local public health: lessons from a mixed-methods evaluation of an academic-public health partnership used in response to COVID-19 - Fielman, Sarah; Elliott, Patricia A.; Codner, Alyson; Abousleiman, Hiba; Cogan, Ally; Wangstrom, Zoë; Greece, Jacey A. (Frontiers in Public Health, 2024)
Introduction The Massachusetts Academic Health Department Consortium (AHD) established the Academic Public Health Volunteer Corps (APHVC) to support Local Health Departments (LHDs, n = 351) to meet rapidly emerging needs during the COVID-19 pandemic through engaging student volunteers. A program evaluation captured lessons learned and informed recommendations for sustainability and future replication. Methods The mixed-methods evaluation leveraged the Consolidated Framework for Implementation Research (CFIR). Data were stratified by LHD engagement with APHVC. Quantitative surveys informed probes for qualitative focus groups and interviews; findings were categorized into CFIR constructs using a deductive approach. Results One-fifth of LHDs (n = 76, 27 used APHVC services, 45 did not) completed the survey. Eleven employees participated in follow-up focus groups or interviews. APHVC filled resource gaps, built capacity, and provided high-quality deliverables. LHDs experienced issues with reliability and communication of volunteers and lacked time to train volunteers. Conclusions CFIR aided in evaluating APHVC in real time, producing actionable recommendations for best practices, dissemination, and future iterations of the program. Results are being used to enhance program effectiveness and sustainability, community health, and health equity across Massachusetts, and may help inform academic practice-based programs across the United States.